Resin composition and sheet molding compound, and alumina particles used in resin composition

By controlling the content of uranium and thorium in aluminum oxide particles and reducing the grain boundary content, the problem of semiconductor equipment sensitivity to α-rays is solved, and a lower α-ray release is achieved, reducing the risk of equipment failure.

JP2025060435APending Publication Date: 2025-04-10SUMITOMO CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024155256
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-09
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

With the miniaturization of semiconductor devices and the reduction of line spacing, the sensitivity of semiconductor devices to α rays increases, and the prior art is difficult to effectively reduce the impact of α rays on semiconductor devices.

Method used

The release of alpha rays is reduced by controlling the content of uranium (U) and thorium (Th) in the aluminum oxide (Alumina) particles and reducing the grain boundary content within the aluminum oxide particles.

Benefits of technology

A lower α-ray release amount than traditional methods is achieved, effectively reducing the risk of failure caused by semiconductor devices due to α-rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060435000001
    Figure 2025060435000001
  • Figure 2025060435000002
    Figure 2025060435000002
  • Figure 2025060435000003
    Figure 2025060435000003
Patent Text Reader

Abstract

To provide a resin composition that contains alumina particles and a resin, the resin composition capable of reducing the α dose as compared with the conventional art.SOLUTION: Provided is a resin composition containing alumina particles and a resin, wherein the alumina particles have a uranium content of less than 550 ppb, a thorium content of less than 10 ppb, and a ratio (L2 / L1) of the total length L2 of the internal grain boundaries to the length L1 of the outer edge of less than 139.1%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to resin compositions and sheet molding compounds, as well as alumina particles for use in the resin compositions. [Background technology]

[0002] Heat generated by passing electricity through electronic components is likely to adversely affect the performance of the electronic components, so it is desirable to dissipate the heat quickly. Therefore, for example, it is desirable for the material constituting the semiconductor sealing member surrounding the IC chip to have high thermal conductivity for heat dissipation. Generally, a composite containing a thermally conductive filler and a resin is used as a thermally conductive filler for heat dissipation. Semiconductor devices are susceptible to the effects of alpha rays, and malfunctions (soft errors) caused by alpha rays are problematic. To solve this problem, it is important to use a resin composition that suppresses the amount of alpha rays emitted as a sealing member. In order to obtain a resin composition with a low amount of alpha rays, it is known to use alumina particles with an extremely small amount of uranium and thorium content (e.g., Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-145336 A [Patent Document 2] JP 2017-110146 A [Patent Document 3] International Publication No. 2022 / 105697 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, semiconductor devices have become more susceptible to the effects of α-rays due to miniaturization and narrowing of wiring pitches of the semiconductor devices. Therefore, resin compositions used in semiconductor encapsulation members are required to reduce the amount of α-rays more than ever before. Patent Documents 1 to 3 disclose the control of the uranium and thorium contents contained in the alumina particles, but do not consider further reducing the amount of alpha rays.

[0005] In view of these circumstances, one embodiment of the present invention aims to provide a resin composition containing alumina particles and a resin, which can reduce the amount of alpha rays emitted compared to conventional resin compositions. Another embodiment of the present invention has an object to provide a sheet-shaped composition (sheet molding compound) comprising such a resin composition. Yet another embodiment of the present invention is directed to providing alumina particles for use in a resin composition. [Means for solving the problem]

[0006] Aspect 1 of the present invention is alumina particles having a uranium content of less than 550 ppb and a thorium content of less than 10 ppb, and a ratio (L2 / L1) of a total length L2 of internal grain boundaries to a length L1 of an outer edge of the alumina particles being less than 139.1%; Resin and The resin composition includes:

[0007] Aspect 2 of the present invention is In the resin composition according to aspect 1, the alumina particles have a particle diameter D100 of 30 μm or less at 100% cumulative from the fine particle side of a volume-based cumulative particle size distribution.

[0008] Aspect 3 of the present invention is The resin composition according to aspect 1 or 2, wherein the elastic modulus is 2.0 GPa or more.

[0009] A fourth aspect of the present invention is The resin composition according to any one of Aspects 1 to 3 includes at least one resin selected from the group consisting of an epoxy resin and a thermoplastic polyimide resin.

[0010] A fifth aspect of the present invention is The resin composition according to embodiment 4, wherein the epoxy resin includes at least one selected from the group consisting of mesogen-based epoxy resins, phenylcyclohexyl-based epoxy resins, naphthalene-based epoxy resins, phenol-based epoxy resins, biphenyl-based epoxy resins, butadiene-based epoxy resins, and bisphenol A-based epoxy resins.

[0011] A sixth aspect of the present invention is The resin composition according to any one of aspects 1 to 5 is used. A sheet molding compound having a thickness of 1000 μm or less.

[0012] A seventh aspect of the present invention is The alumina particles have a uranium content of less than 550 ppb, a thorium content of less than 10 ppb, and a ratio (L2 / L1) of the total length L2 of the internal grain boundaries to the outer edge length L1 of less than 139.1%. Effect of the Invention

[0013] According to one embodiment of the present invention, it is possible to provide a resin composition capable of reducing the amount of α-ray radiation compared to conventional resin compositions. According to another embodiment of the present invention, there is provided a sheet molding compound comprising such a resin composition. According to yet another embodiment of the present invention, alumina particles for use in a resin composition can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The inventors conducted extensive research to reduce the amount of alpha rays emitted from a resin composition. As a result, they discovered for the first time that the amount of alpha rays emitted from a resin composition can be effectively reduced by controlling the uranium (U) content and thorium (Th) content of the alumina particles used in the resin composition to extremely small amounts and reducing the grain boundary content in the alumina particles.

[0015] The mechanism by which the grain boundaries in the alumina particles affect the amount of α-rays emitted from the resin composition is not clear, but is presumed to be as follows. Alpha rays generated from U and Th in the alumina particles can be shielded by the alumina constituting the alumina particles. Here, it is presumed that the grain boundaries in the alumina particles are areas with low alpha ray shielding effect. Therefore, if the grain boundary content of the alumina particles is high, the amount of alpha rays emitted from the alumina particles increases, and the amount of alpha rays emitted from the resin composition using the alumina particles also increases. Therefore, it is believed that by limiting the content of grain boundaries contained in the alumina particles, the amount of alpha rays emitted from the alumina particles can be reduced, and as a result, a resin composition with a low amount of alpha rays can be obtained.

[0016] The resin composition according to the embodiment, the alumina particles used in the resin composition, and the sheet molding compound (SMC) made of the resin composition will be described below.

[0017] [Resin composition] The resin composition according to the present embodiment contains alumina particles and a resin. The alumina particles have a uranium content of less than 550 ppb, a thorium content of less than 10 ppb, and a ratio (L2 / L1) of the total length L2 of the grain boundaries inside the alumina particles to the outer edge length L1 of the alumina particles of less than 139.1%. In this specification, the term "resin composition" is intended to include all of the resin compositions in the liquid state before the resin in the resin composition is cured, the semi-cured state (B stage) in which the resin is semi-cured, and the cured state (C stage) in which the resin is completely cured. Here, the "liquid state" includes compositions in which the resin composition has fluidity, such as resin compositions containing a solvent described below. "Semi-cured" refers to a state in which the resin composition is cured to an extent that it can be handled as a solid, but is not completely cured, and therefore the surface of the resin composition is sticky. "Cured state" refers to a state in which the resin composition can be handled as a solid and has almost no stickiness on the surface.

[0018] The elastic modulus (tensile elastic modulus) of the resin composition is preferably 2.0 GPa or more. The elastic modulus of the resin composition is more preferably 3.0 GPa or more, more preferably 4.0 GPa or more, even more preferably 5.0 GPa or more, particularly preferably 6.0 GPa or more, and most preferably 7.0 GPa or more. The elastic modulus of the resin composition is usually 25.0 GPa or less, and may be 20.0 GPa or less. The elastic modulus is measured in a semi-cured or cured resin composition. In particular, the elastic modulus of the resin composition after curing is preferably 2.0 GPa or more, and a sealing member that can withstand deformation under general use conditions can be formed. The elastic modulus of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014).

[0019] The rupture stress of the resin composition is preferably more than 41.2 MPa, more preferably 50.0 MPa or more, even more preferably 60.0 MPa or more, and particularly preferably 65.0 MPa or more. The rupture stress of the resin composition is measured in a semi-cured or cured state. In particular, the rupture stress of the cured resin composition is preferably more than 41.2 MPa, 50.0 MPa or more, 60.0 MPa or more, or 65.0 MPa or more, in that order. This improves the strength when used as a sealing member, and can also improve the dimensional stability against external energy such as heat. The rupture stress of the resin composition can be calculated from a stress-strain curve obtained in a tensile test in accordance with JIS K7161 (2014). The rupture stress of the semi-cured and cured resin compositions can be increased by adjusting the content of alumina particles and the curing conditions. Usually, the rupture stress of the cured resin composition is higher than that of the semi-cured resin composition.

[0020] Since the alumina particles can reduce the dielectric loss without impairing the flexibility peculiar to the resin, the blending ratio is preferably in the order of 5-75% by volume of resin, 95-25% by volume of alumina particles, or 8-50% by volume of resin, 92-50% by volume of alumina particles, or 10-40% by volume of resin, 90-60% by volume of alumina particles, or 12-40% by volume of resin, and 88-60% by volume of alumina particles, in the total ratio to the entire resin composition. In addition, in the semi-cured and cured resin compositions, the total ratio of the resin and the alumina particles to the entire resin composition is preferably 60% by volume or more, more preferably 70% by volume or more, and even more preferably 80% by volume or more. In addition, in the semi-cured and cured resin compositions, the ratio of the solid content to the entire resin composition is preferably 80% by volume or more, more preferably 90% by volume or more, and even more preferably 95% by volume or more. The solid content of a resin composition refers to what remains as a solid when the resin composition is heated, excluding, for example, the solvent and other components that volatilize upon heating. On the other hand, even if a component is liquid at 25°C, if it is incorporated into the solid content of the resin composition when heated, it is included in the solid content. The proportion of the solid content can be determined, for example, by determining the amount of solvent in the resin composition and subtracting it from the total. The amount of solvent in the resin composition can be measured, for example, by the following method. After measuring the mass W1 (g) of the resin composition, the sample is heated at 150°C for 10 minutes using a total exhaust oven to evaporate all the solvent contained in the sample, and then the sample is left at room temperature for 5 minutes to return to room temperature, and the mass W2 (g) of the sample after heating is measured. The amount of solvent in the resin composition can be determined by subtracting W2 (g) from W1 (g).

[0021] Next, the alumina particles and the resin that constitute the resin composition will be described in detail.

[0022] [Alumina particles] The alumina particles according to this embodiment have the following characteristics. The alumina particles preferably contain α-alumina particles. The α-alumina is expected to have an effect of reducing the amount of α-rays emitted from the alumina particles, and the presence of the α-alumina particles in the alumina particles can improve the effect of suppressing the amount of α-rays emitted from the resin composition. The α-alumina particles are also expected to have an effect of reducing the dielectric loss of the resin composition.

[0023] (Uranium and Thorium Content) The alumina particles have a uranium content of less than 550 ppb and a thorium content of less than 10 ppb. The uranium and thorium contents of the alumina particles are suppressed to very small amounts as described above, so that the amount of α-rays emitted from the alumina particles can be reduced, and as a result, the amount of α-rays emitted from the resin composition can be suppressed. This makes it possible to suppress malfunction of the semiconductor device due to α-rays when used as an encapsulating material for the semiconductor device.

[0024] The uranium content is preferably 300 ppb or less, more preferably 100 ppb or less, even more preferably 50 ppb or less, particularly preferably 30 ppb or less, for example 10 ppb or less, or 5 ppb or less. The lower limit of the uranium content is not particularly limited, but may be 0.1 ppb or more. The thorium content is preferably 8 ppb or less, more preferably 5 ppb or less, and particularly preferably 2 ppb or less. The lower limit of the thorium content is not particularly limited, but may be 0.1 ppb or more. The uranium and thorium contents can be measured using inductively coupled plasma mass spectrometry (ICP-MS).

[0025] (The ratio of the total length L2 of the grain boundaries inside the alumina particle to the outer edge length L1 of the particle) By reducing the grain boundary content in the alumina particles, the shielding effect against alpha rays generated from uranium and thorium in the alumina particles can be improved, and the amount of alpha rays emitted from the alumina particles can be reduced. In this embodiment, the ratio of the total length L2 of the grain boundaries to the length L1 of the outer edge (L2 / L1) is introduced as an index of the content of grain boundaries inside an alumina particle. L1 and L2 are determined by observing a cross section of the alumina particle.

[0026] When the length of the outer edge of one alumina particle is L1 and the total length of the grain boundaries of the alumina particle is L2, it can be said that alumina particles with a small value of L2 / L1 have a small content of grain boundaries and emit a low amount of α-rays. In particular, by making (L2 / L1)(%) less than 139.1%, the amount of α-rays emitted can be further reduced when used as a filler for a resin composition. By reducing the amount of α-rays emitted from the alumina particles, the amount of α-rays emitted from a resin composition containing the alumina particles can also be reduced.

[0027] (L2 / L1) is preferably 120.0% or less, more preferably 100.0% or less, even more preferably 80.0% or less, even more preferably 60.0% or less, particularly preferably 52.0% or less, and most preferably 50.0% or less. The lower limit of (L2 / L1) is not particularly limited, but may be 10.0% or more, for example, 20.0% or more, 30.0% or more, 40.0% or more, or 43.0% or more. When the lower limit of L2 / L1 is within the above range, the interaction between the particles and the resin becomes easier to work, and in particular, the mechanical strength such as the breaking stress of the resin composition after semi-curing and curing is easily increased. In order to control this L2 / L1 within a suitable range, single crystal raw material particles may be used.

[0028] Furthermore, the fewer the grain boundaries and cavities inside the alumina particles, the lower the dielectric loss of the alumina particles. Therefore, by controlling (L2 / L1) to less than 139.1%, a resin composition with low dielectric loss can be obtained.

[0029] The "total length L2 of grain boundaries" refers to the sum of the grain boundaries contained inside an alumina particle, and does not include the outer edge of the alumina particle. The total length L2 of grain boundaries is the sum of the total length L3 of grain boundaries inside an alumina particle and the total length L4 of the inner wall of the cavity (if there is a cavity inside the alumina particle) (i.e., L2 = L3 + L4).

[0030] (Particle size of alumina particles) The alumina particles preferably have a particle diameter D100 of 30 μm or less, which is 100% cumulative from the fine particle side of the cumulative particle size distribution based on volume. By using such alumina particles, a resin composition with lower dielectric loss can be obtained. D100 is preferably 30 μm or less, more preferably less than 20 μm, and particularly preferably 10 μm or less. The lower limit of D100 is not particularly limited, but may be 0.1 μm or more. Furthermore, the alumina particles preferably have a particle diameter D50 of 50% cumulative from the fine particle side of the volume-based cumulative particle size distribution of 20 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, and particularly preferably 3 μm or less.

[0031] In one embodiment of the present invention, the alumina particles preferably have a ratio D90 / D50 of the particle diameter D90 (hereinafter sometimes simply referred to as "D90") of the cumulative 90% of the number from the fine particle side of the cumulative particle size distribution to the particle diameter D50 (hereinafter sometimes simply referred to as "D50") of the cumulative 50% of the number from the fine particle side of the cumulative particle size distribution, which is 5.0 or less. This makes the particle size distribution sharp, making it easier for moderate interaction to occur between the particles and the resin, and in particular, making it easier to increase the mechanical strength, such as the breaking stress, of the resin composition after semi-curing and curing. For example, D90 / D50 is more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 1.5 or less.

[0032] On the other hand, if the particle size distribution of the alumina particles is broad to some extent, the filling property is improved by allowing small particles to enter the gaps between the large particles, and more alumina particles can be kneaded into the resin, which can improve the dimensional stability and breaking stress against external energy such as heat. Therefore, D90 / D50 is preferably 1.1 or more, more preferably 1.2 or more, and even more preferably 1.3 or more.

[0033] The particle diameters D100, D90 and D50 of the alumina particles can be determined by measuring the particle size distribution of the alumina particles by a laser diffraction method using, for example, a laser particle size distribution measuring device such as "Microtrac MT3300EXII" manufactured by Microtrac Bell Co., Ltd. D100 being 30 μm or less means that the particle diameter of all the alumina particles is 30 μm or less, and that substantially no alumina particles having a particle diameter of more than 30 μm are included. The particle size of the alumina particles in the resin composition can be measured by removing the resin contained in the resin composition, for example, by dissolving it in an organic solvent or by heating it to a temperature of 500°C or higher to pyrolyze the resin, isolating only the alumina particles, and using the alumina particles.

[0034] Another method for determining D100, D90, and D50 of alumina particles is a method using image analysis. The resin composition may be subjected to cross-sectional observation with an SEM, and all alumina particles contained in a predetermined observation area (e.g., 200 μm×200 μm) may be subjected to image analysis, and the particle diameters equivalent to D100, D90, and D50 may be calculated based on the measurement results of their particle diameters (circle-equivalent diameters).

[0035] [Method of manufacturing alumina particles] The alumina particles according to this embodiment can be produced, for example, by the method described below.

[0036] (Raw alumina) The raw alumina is produced by a known method, such as the Bayer method, the ammonium alum method, the ammonium aluminum carbonate hydroxide method (AACH method), the solvent extraction method, the organoaluminum hydrolysis method (aluminum alkoxide method), the CZ method, the Verneuil method, the chiroporous method, the Bridgman method, the EFG method, or other melt growth methods.

[0037] In the case of the Bayer process, raw alumina can be produced by calcining aluminum hydroxide obtained from bauxite. In addition, the ammonium alum process, the AACH process, the solvent extraction process, and the aluminum alkoxide process are preferable because they can produce high-purity raw alumina with low uranium and thorium contents. If raw alumina produced by these methods, with a uranium content of less than 550 ppb and a thorium content of less than 10 ppb, is used to produce alumina particles, it is preferable because alumina particles with low uranium and thorium contents can be obtained.

[0038] (Crushing raw alumina) In order to easily obtain alumina particles of a desired size by flame melting, the raw alumina is pulverized to obtain an alumina raw powder to be subjected to flame melting. The raw alumina can be pulverized by a known method such as a vibration mill, a bead mill, a ball mill, or a jet mill, and may be pulverized in either a dry or wet state.

[0039] In the above-mentioned pulverization, a surface protective agent may be used. The surface protective agent may not only protect the surface of the alumina raw material powder after pulverization, but also have the function of inactivating the surface of the alumina raw material powder. The surface protective agent can reduce the aggregation of the alumina raw material powders themselves due to its function of inactivating the surface, and is therefore suitable for obtaining alumina particles of a desired particle size after flame fusion using raw material alumina with a high BET specific surface area that is prone to aggregation. Suitable surface protective agents include, for example, monohydric alcohols such as methanol, ethanol, 1-propanol, and 2-propanol; glycols such as ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol; amines such as triethanolamine; and higher fatty acids such as palmitic acid, stearic acid, and oleic acid. Of these surface protective agents, one type may be used alone, or two or more types may be used in combination. Of these, glycols are preferred, and in particular, one or more types of ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol are preferred.

[0040] For example, polyethylene glycol and polypropylene glycol, which are preferably used as surface protective agents, are not particularly limited in terms of their molecular weight, but liquid ones with an average molecular weight of about 200 to 600 are preferred for ease of addition.

[0041] The amount of the surface protective agent added is preferably 0.01 parts by mass or more in order to fully exert the effect of the surface protective agent when the raw material alumina is taken as 100 parts by mass, and is preferably 10 parts by mass or less because the effect of the surface protective agent becomes saturated if the amount of the surface protective agent added is too large. The amount of the surface protective agent added is more preferably 0.05 to 8 parts by mass, and even more preferably 0.1 to 5 parts by mass.

[0042] (Flaming) The flame fusion method is a method in which raw alumina is sprayed into a flame, turned into droplets, and then cooled and solidified. According to the flame fusion method, alumina particles can be obtained while maintaining the particle size of the raw alumina. In the flame fusion method, the temperature of the flame fusion furnace is preferably 1000°C or higher. In the flame fusion method, the raw material supply rate can be appropriately adjusted, but by setting it to preferably 50 kg / h or less, more preferably 10 kg / h or less, the amount of thermal energy applied to the alumina particles can be controlled within a specified range, making it easier to obtain alumina particles that meet the above-mentioned specified requirements.

[0043] After the flame melting, the alumina particles are collected using a cyclone or a bag filter and classified to obtain alumina particles having desired properties.

[0044] [resin] The resin used in the resin composition preferably contains one or more selected from the group consisting of epoxy resins and thermoplastic polyimides, and more preferably contains an epoxy resin. Preferred epoxy resins include mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins. The mesogenic epoxy resin is an epoxy resin having a mesogenic group, and is preferably a resin that exhibits a phase transition temperature in the temperature range of 100°C to 200°C to be sealed and exhibits liquid crystallinity. The resin contained in the resin composition may contain one or more epoxy resins. That is, the resin contained in the resin composition may contain one or more epoxy resins selected from the group consisting of mesogenic epoxy resins, phenylcyclohexyl epoxy resins, naphthalene epoxy resins, phenolic epoxy resins, biphenyl epoxy resins, butadiene epoxy resins, and bisphenol A epoxy resins, and may further contain a thermoplastic polyimide. These resins are expected to have the effect of blocking alpha rays emitted from alumina particles, and because they have low dielectric loss, it is possible to obtain a resin composition with even lower alpha radiation dose and even lower dielectric loss.

[0045] Furthermore, these resin compositions may be appropriately mixed with known additives such as plasticizers, curing agents, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weather resistance agents, antiblocking agents, antistatic agents, leveling agents, and release agents, either singly or in combination, as long as the effects of the invention are not impaired. In addition, as an embodiment of the present application, the resin composition (particularly, a resin composition in a liquid state or a semi-cured state) may contain a solvent, and when the resin composition contains a solvent, it is easy to flow, can be easily deformed to match the fine structures of IC chips and substrates, and can seal dense structures without gaps. As the solvent, known solvents can be used, and are not limited as long as the resin can be dissolved therein, and examples thereof include alcohol-based solvents, ketone-based solvents, ether-based solvents, ester-based solvents, amine-based solvents, amide-based solvents, halogen-based solvents, hydrocarbon-based solvents, and nitrile-based solvents. Ketone-based solvents and ester-based solvents are preferred from the viewpoint of being good solvents for epoxy resins and excellent coating properties of the resulting resin composition.

[0046] In a preferred embodiment of the present invention, the resin composition comprises alumina particles, an epoxy resin, a solvent, and a hardener, such as an amine-based hardener such as 4,4-diaminodiphenylmethane.

[0047] [Method of producing resin composition] A method for producing the resin composition will be described. A resin composition can be obtained by mixing the alumina particles according to the present embodiment with a resin using a commonly used known method. For example, when the resin is liquid (e.g., liquid epoxy resin, etc.), the resin composition can be obtained by mixing the liquid resin, alumina particles, and a curing agent, and then curing with heat or ultraviolet light. Known curing agents and known methods can be used as the curing agent, mixing method, and curing method. On the other hand, when the resin is solid (e.g., epoxy resin, polyolefin resin, acrylic resin, etc.), the alumina particles and the resin are mixed, and then kneaded by a known method such as melt kneading, or the resin, alumina particles, and a curing agent are dissolved and mixed in a solvent to obtain the desired resin composition. The resin composition may contain a solvent.

[0048] The resin composition according to this embodiment includes a resin composition in all states, including a liquid state before the resin in the resin composition is cured, a semi-cured state (B stage) in which the resin is semi-cured, and a cured state (C stage) in which the resin is completely cured. The resin composition in a liquid state includes a compound in which alumina powder and a resin are mixed in a predetermined mixing ratio, a mixture obtained by mixing the compound, and a molded product obtained by molding the mixture. The semi-cured resin composition includes a resin composition obtained by semi-curing a resin contained in a mixture or a molded product. The cured resin composition includes a resin composition obtained by completely curing a resin contained in a mixture, a molded product, or a semi-cured product.

[0049] [Sheet Molding Compound (SMC)] The resin composition according to the embodiment can be used to provide a sheet molding compound (SMC). The SMC is a resin composition molded into a sheet. The SMC is preferably one that has flowability when heated and pressurized, and may be in a semi-cured state. The thickness of the SMC is preferably 1000 μm or less, and when incorporated into a semiconductor device, the semiconductor device can be made smaller and lighter, and when sealing an IC chip, the sealing performance can be improved. The thickness is more preferably 800 μm or less, even more preferably 600 μm, even more preferably 500 μm or less, particularly preferably 400 μm or less, and particularly preferably 300 μm or less. The lower limit of the thickness is not particularly limited, but from the viewpoint of the dimensions of SMCs generally used and improving the sealing performance of IC chips, it may be, for example, 10 μm or more, 50 μm or more, or even 100 μm or more, or 150 μm or more.

[0050] The SMC can be prepared by a known method. As an example, an uncured resin composition is applied onto a substrate, a protective film is placed thereon, and the resin composition is semi-cured. As another example, an uncured resin composition containing a solvent is applied onto a substrate, the solvent is removed from the resin composition by drying or the like, and then a protective film is placed. When using the SMC, the protective film is peeled off, the SMC is pressed against a wafer or the like, the substrate is removed, and the SMC is post-cured.

[0051] The resin composition and SMC of the present invention have a low alpha radiation dose and low dielectric loss, and are therefore suitable as sealing materials for semiconductor elements. EXAMPLES

[0052] [Creation of alumina particles] The alumina particles (A to E) used in the resin compositions of Samples No. 1 to 8 were prepared as follows.

[0053] (Alumina particles A and B used in samples No. 1 to 5) As the alumina particles, the following alumina particles A (used for samples Nos. 3 to 5) and alumina particles B (used for samples Nos. 1 and 2) were prepared.

[0054] The raw alumina used was γ-alumina obtained by the ammonium alum method (the average particle size of the primary particles calculated from the BET specific surface area value below was 13 nm). The BET specific surface area of ​​this γ-alumina measured by the nitrogen adsorption method was 120 m 2 Before pulverization, 4% by mass of propylene glycol was added as a surface protective agent to the raw alumina and mixed.

[0055] Next, the alumina was processed using a jet mill pulverizer (horizontal jet mill pulverizer PJM-280SP manufactured by Japan Pneumatic Mfg. Co., Ltd.) under the conditions of a feed rate of the raw alumina of 30 kg / h and a gauge pressure of the air supply port during pulverization of 0.5 MPa, to obtain an alumina raw powder with an average secondary particle size of approximately 2 μm.

[0056] The obtained alumina raw material powder was put into a flame melting furnace and melted to obtain spherical alumina particles. The atmospheric temperature in the flame melting furnace was set to 1250°C, and the raw material supply rate was set to 5 kg / h. The obtained alumina particles were collected by a cyclone and classified by cyclone classification to remove particles of 20 μm or more to obtain alumina particles A (D50=5.1 μm, used for samples No. 3 to 5). Furthermore, particles of 10 μm or more were removed to obtain alumina particles B (D50=2.3 μm, used for samples No. 1 to 2).

[0057] (Alumina particles C used in sample No. 6) For sample No. 6, alumina particles C prepared by the following procedure were used. Alumina raw material particles made of single crystal alumina with a D50 of 3.5 μm were prepared, and then charged into a flame melting furnace to melt and obtain spherical alumina particles. The obtained alumina particles were classified by cyclone classification to remove particles of 20 μm or more, thereby obtaining alumina particles C.

[0058] (Alumina particle D used in sample No. 7) For sample No. 7, alumina particles (alumina particles D) manufactured by Denka DAW05 were used.

[0059] (Alumina particles E used in sample No. 8) For sample No. 8, alumina mixed particles (alumina particles E) prepared by mixing alumina particles B and AA-18 manufactured by Sumitomo Chemical Co., Ltd. in a mass ratio of 9:1 were used.

[0060] The alumina particles used in each sample were subjected to the following measurements.

[0061] [Particle size distribution of alumina particles] The particle size distribution of the alumina particles was measured by the laser diffraction method using a Microtrack MT3300EXII laser particle size distribution measuring device manufactured by Microtrack Bell Co., Ltd. The D50, D90 and D100 were obtained from the particle size distribution measurement results. As a sample for measurement, alumina particles to be measured were added to a 0.2 mass% sodium hexametaphosphate aqueous solution so that the laser scattering intensity was appropriate, and the alumina particle dispersion was dispersed for 5 minutes using the built-in ultrasonic of 40W. The refractive index of alumina was set to 1.76.

[0062] [Uranium and thorium content of alumina particles] The uranium content (U amount) and thorium content (Th amount) contained in the alumina particles were measured as follows. First, the alumina particles were put into a mixed aqueous solution of sulfuric acid and phosphoric acid, and heated to dissolve the alumina particles, to prepare an aqueous solution. Then, the aqueous solution was contacted with a cyclohexane solution of tributyl phosphate, which is commonly used as an extractant for uranium, to extract the uranium contained in the aqueous solution. Then, the uranium transferred to the aqueous phase by back-extraction by contacting again with pure water was measured by the intensities of U238amu and Th232amu using ICP-MS. A standard solution manufactured by SPEX was used to create a calibration curve.

[0063] [BET specific surface area of ​​alumina particles] The specific surface area was measured using a Shimadzu Flowsorb III 2310 specific surface area measuring device, and the nitrogen adsorption BET specific surface area was determined by the single point nitrogen adsorption method according to the method specified in JIS-Z8830 (2013). The measurement conditions were as follows: Carrier gas: Nitrogen / helium mixed gas Filling sample amount: 0.1g Sample pretreatment conditions: 200°C for 20 minutes Nitrogen adsorption temperature: Liquid nitrogen temperature (below -196℃) Nitrogen desorption temperature: room temperature (approximately 20°C)

[0064] [Measurement of the outer edge length L1 of an alumina particle and the total length L2 of the grain boundary inside the particle] Cross-sectional observation specimens were prepared using alumina particles of samples No. 1 to 6. In preparing cross-sectional observation specimens, the alumina particles were embedded in resin, and then the resin and alumina particles were cut with a diamond cutter. Then, Pt was evaporated onto the cross section as a protective film, the cross section was prepared by Ar ion milling, and the specimen was fixed to the SEM specimen stage with Cu double-sided tape, and SEM-EBSD measurement was performed without evaporation. The observation position was determined so that two or more alumina particles were completely within the observation area (i.e., two or more alumina particles did not come into contact with the frame of the observation area). All of the measured alumina particles were α-alumina particles.

[0065] The following equipment was used for sample preparation and EBSD measurement: ·Equipment used Ion milling device: IM-4000 (manufactured by Hitachi, Ltd.) Ion sputtering device: E-1030 (manufactured by Hitachi, Ltd.) Ultra-high resolution field emission scanning electron microscope: JSM-7800F Prime (manufactured by JEOL Ltd.) Backscattered electron diffraction equipment: Digiview V (TSL)

[0066] The EBSD measurement conditions were as follows: ·Measurement area: 500.0μm×400.0μm Acceleration voltage: 20.0 kV Magnification: x500 ·Vacuum degree: 30Pa

[0067] In the obtained EBSD image, two or more alumina particles that were not in contact with the frame of the observation area were selected, and the outer edge length L1 of each alumina particle was averaged using image processing software Image J (National Institute of Health). The "total grain boundary length L2" is the sum of the grain boundaries contained inside the alumina particle, and does not include the outer edge of the alumina particle. The total grain boundary length L2 was calculated by adding the total length of the grain boundaries inside the alumina particle and the total length of the inner wall of the cavity (if there is a cavity inside the alumina particle).

[0068] The ratio of the total grain boundary length L2 to the outer edge length L1 (L2 / L1) is expressed as a percentage (%). The more grain boundaries and cavities there are inside the alumina particle, the higher the value of L2 / L1 (%).

[0069] [Amount of alpha rays emitted from alumina particles] The amount of alpha radiation emitted from the alumina particles was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas was PR-10 gas (Ar90%, CH 4 10%) was used.

[0070] [Preparation of resin composition] Alumina particles, resin, etc. were kneaded to prepare resin compositions (samples No. 1 to 8). The types of resins used are shown in Table 1, and the amounts of alumina particles used are shown in Table 3. In addition, the elastic modulus of the resin not containing alumina particles was measured when cured, and is shown in the "Elastic Modulus" column of "Resin" in Table 3. Specifically, the resin compositions of Samples No. 1 to 8 were prepared according to the following preparation method. In Table 3, "resin composition" refers to the resin composition in a cured state.

[0071] (Samples No. 1-4, 6-8) (1) Preparation of varnish A 30% by mass mixed solution was prepared by dissolving the resin shown in Table 1 in the solvent shown in Table 1. Furthermore, a curing agent (4,4-diaminodiphenylmethane (manufactured by TCI)) was added in an amount of 0.074% by mass relative to 100% by mass of the mixed solution to prepare a varnish.

[0072] (2) Preparation of alumina / varnish mixture Alumina particles were added to the obtained varnish and kneaded using a planetary centrifugal mixer (manufactured by Thinky Corporation) to prepare an alumina / varnish mixture.

[0073] (3) Film formation The obtained alumina / varnish mixture was applied onto a PET substrate, and a film was formed using an applicator so that the film thickness after thermal curing would be 150 to 200 μm, thereby obtaining a resin composition before curing.

[0074] (4) Heat curing The obtained resin composition before curing was left to stand at room temperature for 1 hour, then heated at 140°C for 15 minutes, and further vacuum press molded at 140°C for 20 minutes at a pressure of 0.5 MPa using a press molding machine, and then heated at 180°C for 120 minutes at normal pressure to be thermally cured. In this way, cured resin compositions (samples No. 1 to 4, 6 to 8) were obtained. In the resin compositions of samples No. 1 to 4, and 6 to 8, the proportion of solids in the entire resin composition was 95% by volume or more.

[0075] (Sample No. 5) (1) Preparation of varnish The resins shown in Table 1 were dissolved in the solvents shown in Table 1 to prepare 12% by mass mixed solutions.

[0076] (2) Preparation of alumina / varnish mixture Alumina particles were added to the obtained varnish and kneaded using a planetary centrifugal mixer (manufactured by Thinky Corporation) to prepare an alumina / varnish mixture.

[0077] (3) Film formation The obtained alumina / varnish mixture was applied onto a PET substrate, and a film was formed using an applicator so that the film thickness after thermal curing would be 150 to 200 μm, thereby obtaining a resin composition before curing.

[0078] (4) Heat curing The obtained resin composition before curing was heated at 120°C for 3 hours, and then heated from 25°C to 360°C in a nitrogen atmosphere and heated at 360°C for 30 minutes to be thermally cured, thereby obtaining a cured resin composition (sample No. 5).

[0079] [Table 1]

[0080] Details of the resin types listed in Table 1 are as follows:

[0081] Mesogenic epoxy resin (A) It is a prepolymer obtained by reacting trans-4-{4-(2,3-epoxypropoxy)phenyl}cyclohexyl 4-(2,3-epoxypropoxy)benzoate (an epoxy resin represented by the structural formula below) with 6-hydroxy-2-naphthoic acid.

[0082] [ka]

[0083] Mixture of JP-100 and HP6000 The resin was prepared by mixing JP-100 (manufactured by Nippon Soda Co., Ltd.), an epoxidized polybutadiene, and HP-6000 (manufactured by DIC Co., Ltd.), a naphthalene-based epoxy resin, in a mass ratio of 1:9.

[0084] Thermoplastic polyimide (TPI) The thermoplastic polyimide used was a compound synthesized under the following conditions. 9.87g (46.5mmol) of m-Tb and 122.35g (418.5mmol) of TPE-R were dissolved in 1890g of DMAc, and then 30.26g (138.7mmol) of PMDA and 95.25g (323.7mmol) of BPDA were added in that order and stirred for 3 hours at 20°C under a nitrogen atmosphere. The molar ratio of the diamine monomer to the acid dianhydride monomer used was 1.01.

[0085] [Dielectric loss of resin composition] Regarding the cured resin compositions (samples No. 1 to 8), The dielectric loss of the resin composition was measured under the following measurement conditions. Measurement equipment: Network analyzer 8720ES (Agilent Technologies) - Test piece size: 50mm x 50mm ·Measurement frequency: 12GHz Test environment: 22℃ / 59%RH

[0086] [α-ray dose emitted from resin composition] The amount of α-rays emitted from the resin composition was measured using a measuring device Model 1950 (manufactured by Alpha Sciences). The measurement area of ​​the sample was 1000 cm 2 The measurement time was 99 hours, and the counting gas was PR-10 gas (Ar90%, CH 4 10%) was used.

[0087] [Elastic modulus of resin composition] The elastic modulus of the resin composition was measured in accordance with JIS K7161 (2014). Specifically, a tensile test was performed on the cured resin composition under the following conditions, and the elastic modulus was calculated by analyzing the obtained stress-strain curve. Test equipment: Autograph AGS-X (Shimadzu Corporation) Load cell: 1kN - Test piece size: 100mm x 10mm Test environment: 22℃ / 59%RH Analysis software: TRAPEZIUMX

[0088] [Breaking stress of resin composition] The breaking stress of the resin composition was calculated by analyzing the stress-strain curve obtained in the above tensile test. The breaking stresses of the resin compositions of Samples Nos. 1 to 4 and 7 were 70.2 MPa, 78.4 MPa, 47.4 MPa, 63.8 MPa, and 41.2 MPa, respectively.

[0089] The results of various measurements of the alumina particles are shown in Table 2, and the types of resins used (and their elastic moduli) and the results of various measurements of the resin compositions are shown in Table 3. In the table, "-" indicates that no measurement was performed.

[0090] [Table 2]

[0091] [Table 3]

[0092] The measurement results are discussed below. The resin compositions of Samples 1 to 4 and 6, which satisfy the requirements of the present embodiment, emitted low amounts of α-rays. On the other hand, the resin composition of Sample 7, which does not satisfy the requirements of the present embodiment, emitted high amounts of α-rays.

[0093] From the particle size distribution measurement results, it was confirmed that alumina particles A to C used in the resin compositions of samples No. 1 to 6 (Examples) did not contain particles of 20 μm or more (i.e., D100 was less than 20 μm), and among them, alumina particles B did not contain particles of 10 μm or more. On the other hand, it was confirmed that alumina particles D and E used in the resin compositions of samples No. 7 to 8 (Comparative Examples) contained particles of 20 μm or more (i.e., D100 was 20 μm or more).

[0094] Samples Nos. 1 to 6 had low dielectric loss, and in particular, Samples Nos. 1, 3, and 6 had extremely low dielectric loss. On the other hand, Samples Nos. 7 and 8 had high dielectric loss.

Claims

1. alumina particles having a uranium content of less than 550 ppb, a thorium content of less than 10 ppb, and a ratio (L2 / L1) of a total length L2 of internal grain boundaries to a length L1 of an outer edge of the alumina particles being less than 139.1%; Resin and A resin composition comprising:

2. The resin composition according to claim 1 , wherein the alumina particles have a particle diameter D100 of 30 μm or less at 100% cumulative from the fine particle side of a volume-based cumulative particle size distribution.

3. The resin composition according to claim 1, having an elastic modulus of 2.0 GPa or more.

4. The resin composition according to claim 1 , wherein the resin comprises at least one selected from the group consisting of an epoxy resin and a thermoplastic polyimide resin.

5. 5. The resin composition according to claim 4, wherein the epoxy resin comprises at least one selected from the group consisting of mesogen-based epoxy resins, naphthalene-based epoxy resins, phenylcyclohexyl-based epoxy resins, phenol-based epoxy resins, biphenyl-based epoxy resins, butadiene-based epoxy resins, and bisphenol A-based epoxy resins.

6. The resin composition according to any one of claims 1 to 5 is used. A sheet molding compound having a thickness of 1000 μm or less.

7. Alumina particles having a uranium content of less than 550 ppb, a thorium content of less than 10 ppb, and a ratio (L2 / L1) of a total length L2 of internal grain boundaries to a length L1 of an outer edge of the alumina particles being less than 139.1%.

Citation Information

Patent Citations

  • Spherical alumina powder

    JP2015145336A

  • Epoxy resin composition

    JP2017110146A

  • Drive system for medical vacuum negative-pressure machine

    WO2022105697A1